A study on the practice of staff training in quantity surveying firms - Roslan, Huda; Tan, Chin Keng; Yeoh, Kah Ching (IIUM Press, 2011)
This research aims to study the practice of staff training in Malaysia. The study is conducted in two stages. Stage one is the literature review. Stage two is the interviews with the principal and staff of QS firms. Findings from the study indicate that majority of the QS firms practice staff training. The QS firms have policy and budgets for staff training. Furthermore, majority of the QS firms practice external training by sending the staff to conference, convention, seminars and workshop. A small number of the firms conduct in-house training. The training is basically related to works of QS and technical knowledge.